Pemilihan Dan Penggunaan Mesh Pada Hernia - Farida Mustafavi; Muhammad Sayuti (Calory Journal Medical Laboratory Journal, 2023)
Hernia is the protrusion or protrusion of the contents of a cavity through a defect or a weak part of the cavity wall concerned. In an abdominal hernia, the abdominal contents protrude through a defect or a weak part of the musculoaponeurotic layer of the abdominal wall. The hernia consists of a ring, pouch and hernia contents (1). The incidence rate of inguinal hernia (medial and lateralis) is 10 times more than femoral hernia and both have a percentage of about 75- 80% of all types of hernia, incisional hernia 10 %, ventral hernia 10 %, umbilical hernia 3 %, and other hernia about 3%. Hernia surgery using a mesh is one of the most common actions performed in general surgery. With the installation of a mesh on an inguinal hernia can reduce the recurrence rate by less than 5%. This technique can also reduce the presentation of postoperative pain so that patients can quickly return to their daily activities. Another advantage with using the mesh method is that it reduces the pressure on the seam line and reduces long-term follow-up.